The human right to education and health: A reflexive perspective of Frankfurt's critical theory - Rosa , Cleudes Maria Tavares; Kern , Maurides Macêdo; Silva , Alessandro Rezende da (Seven Editora, 2023)
The work tensions the categories education, training and human rights, critically relating them to the constant prediction of universalist international norms. These neglect their own imposition in diverse socio-cultural contexts. In this way, they sustain, by uncriticality, the ideology of the groups of economic power in capitalist society. Critical education is what will contribute to a critical interpretation of human rights. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-125